Sistem Pengenalan Warna Berbasis OpenCV untuk Mendukung Aksesibilitas pada Individu dengan Buta Warna (International Forum of Researchers and Lecturers, 2024)
This study develops an OpenCV-based color recognition system to support individuals with color blindness, aiming to enhance their independence in recognizing colors. The User-Centered Design (UCD) methodology was employed, allowing direct user feedback for development tailored to their needs. The developed system showed significant capability in detecting and identifying colors with a camera and analyzing them using OpenCV. The system provides text output to facilitate use by color-blind individuals and has been tested across various lighting conditions and devices. However, there is still potential for improvement, especially in dealing with fluctuations in extreme lighting conditions and integrating voice output for better auditory assistance. Recommendations for further development include the integration of voice recognition, improvements to the color detection algorithm, and further testing with a diverse user group. This will enhance the system's functionality, accuracy, and accessibility for everyone, particularly those suffering from color blindness.